Effect of pH and applied potential on the adsorption of DNA on highly oriented pyrolytic graphite electrodes. Atomic force microscopy surface characterisation - Brett, Ana Maria Oliveira (2003)
Single-stranded and double-stranded DNA electrochemical biosensors prepared by adsorption during 3 min on HOPG, with or without an applied potential, at pH 5.3 and 7.0, were characterised by MAC mode AFM. During adsorption DNA condenses on the substrate forming complex network films with pores exposing the HOPG surface. The thin films formed in pH 5.3 acetate buffer always presented a better coverage of the HOPG surface with DNA molecules than films formed in pH 7.0 phosphate buffer. The application of a positive potential of 300 mV during adsorption enhanced the robustness and stability of the DNA films with the formation of bigger network holes and a more condensed and compact self-assembled DNA lattice. The knowledge of the morphology of adsorbed DNA on electrode surfaces explains non-specific adsorption on the electrode surface and can be used to improve and develop DNA-electrochemical biosensors.